Aerobic Bioremediation of Selenite in Marine and Freshwater Environments Via Intracellular Selenium Nanoparticle Formation by Pseudomonas Frigusceleri mpc6 in Glycerol-Fed Continuous Bioreactors - Donoso-Garcia, P; Lauzurique-Guerra, y; Poblete-Castro, I; Orellana-Saez, M (Academic Press, 2025)
Bacterial remediation of selenite (SeO32−) in contaminated water is a cost-effective approach, but high concentrations of this oxyanion can limit its efficiency. Microorganisms can reduce selenite to elemental selenium, typically leading to the formation of selenium nanoparticles (SeNPs). However, developing continuous aerobic selenite bioremediation processes for industrial and natural water systems remains a challenge. Here, we harnessed the metabolic capacity of the Antarctic extremophile Pseudomonas frigusceleri MPC6 to intracellularly biosynthesize SeNPs from selenite in aerobic bioreactors. Axenic batch bioreactors removed selenite at a rate of 0.42 mM/h using glycerol as a carbon source, but only in the presence of diluted lysogeny broth. According to SEM-EDS and XPS analyses, the biosynthesized SeNPs were primarily composed of selenium, with an average size of 147 nm and a zeta potential of −46 mV. Continuous aerobic bioreactors significantly enhanced selenite removal, achieving a rate of 0.89 mM/h and forming intracellular SeNPs with properties similar to those produced in batch reactors. To remediate 2 mM selenite in seawater, non-sterile continuous bioreactors were operated this time feeding crude glycerol from the biodiesel industry. This system achieved a remediation rate of 0.22 mM/h, producing intracellular SeNPs with an average size of 348 nm under steady-state conditions. 16S rRNA gene sequencing analyses confirmed that P. frigusceleri remained the dominant bacterial member, comprising 99.9 % of the microbial community throughout the unsterile remediation process. These findings underscore the potential of using extremophiles like P. frigusceleri for continuous detoxification of selenite in diverse aquatic systems while valorizing the oxyanion into SeNPs. © 2025 Elsevier Ltd